Pre-Service English Teachers’ Perceptions and Motivations in Continuing Their Profession as EFL Teachers - Naja, Shilvia Lailin (RETAIN : Journal of Research in English Language Teaching, 2023)
Perception significantly motivates English Language Education Study Program students to become English as a Foreign Language (EFL) teachers. This study investigates pre-service English teachers' perceptions of continuing as English teachers as a professional choice and the motivational factors that influence pre-service teachers to continue as English teachers as a professional choice. The investigation is phenomenological. A qualitative research approach using a questionnaire was conducted with a sample of 86 students of an English Language Education study programme who were given a questionnaire to be filled in through the G-Form link, and 21 students returned the questionnaire. Then, this research also conducted semi-structured interviews with a sample of four English Language Education Study Programme students of the 2019 cohort of one state university in Surabaya who had completed the teaching practice programme (PLP) in semester seven. The results suggest that the participants chose to become English teachers because of internal, external, and altruistic factors. Likewise, those who decided not to become English teachers were influenced by internal, external, and altruistic factors. These findings contradict previous research on teacher motivation in developing countries and what is commonly believed in Indonesia. Furthermore, having completed a teaching practise program and seven semesters of lectures has had a significant impact on the 2019 cohort's perceptions of the English Language Education Study Program. The majority of those given the questionnaire had a favourable view of continuing to become an English teacher as a career. Finally, this study suggests understanding their perceptions. So that educational institutions can provide tailored support, guidance, and opportunities to cultivate and maintain the iv perceptions of ELE students in pursuing their future profession as EFL teachers.